2009
DOI: 10.3122/jabfm.2009.06.070098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression Symptoms in Outpatients with a Complaint of Headache

Abstract: Purpose: This case-control study was designed to determine whether adults who present to a primary care office with a chief complaint of headache have more reported symptoms of depression than adults presenting with other problems.Methods: Adult, English-speaking patients who presented to a primary care office with a chief complaint of headache were matched to adult patients of the same age and sex who presented with problems other than headache. All participants completed the PRIME-MD 9-item Patient Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
2
13
1
Order By: Relevance
“…On the other hand, 1.7% out of remained patients who chiefly complained of symptoms other than headache were depression, suggesting approximately 5 times higher prevalence of depression in patients with headache. Marlow et al [14] have reported that 32% of patients with headache were depression whereas 12% patients without headache were depression, indicating 3-times higher prevalence of depression in patients with headache, supporting our present results. Chung et al [15] have demonstrated that patients who presented with a chief complaint of headache in the outpatient family practice setting were found to have a high prevalence of depression.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, 1.7% out of remained patients who chiefly complained of symptoms other than headache were depression, suggesting approximately 5 times higher prevalence of depression in patients with headache. Marlow et al [14] have reported that 32% of patients with headache were depression whereas 12% patients without headache were depression, indicating 3-times higher prevalence of depression in patients with headache, supporting our present results. Chung et al [15] have demonstrated that patients who presented with a chief complaint of headache in the outpatient family practice setting were found to have a high prevalence of depression.…”
Section: Discussionsupporting
confidence: 91%
“…Depressive symptoms include comorbid conditions such as depression, anxiety, or emotional disorders, back or neck disorders 6 ) , migraines or chronic headaches 7 ) , stomach or bowel disorders 8 ) , and insomnia 9 ) . To determine the total burden of depressive symptoms, it is necessary to take these comorbid conditions into account.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous studies (Kroenke, Spitzer, & Williams, 2001;Marlow et al, 2009; U.S. Department of Veterans Affairs, 2009), patients with scores of ≥5 were diagnosed as depressed and those <5 free of depression. The technical justification for doing so was to construct 2 × 2 tables to enable statistical analysis.…”
Section: Data Collectionmentioning
confidence: 89%
“…Rodin and Voshart (1986) reported the occurrence of mild to moderate symptoms of depression in up to one third of medical in-patients. Previous studies by MacHale (2002) and Marlow, Kegowicz, and Starkey (2009) further reported different prevalence rates of depressive illness in different disease conditions. They reported prevalence rates of about 25% in patients with diabetes and cardiac or neurological disease and 32% among patients with headache in Arizona.…”
Section: Introductionmentioning
confidence: 99%